An overview of research on mechanisms of resistance in maize to spotted stem borer - Kumar, H.
Sumario (En)
Ilus.; 54 ref.
Keywords: ZEA MAYS; FITOMEJORAMIENTO; RESISTENCIA A LAS PLAGAS; LEPIDOPTERA; GERMOPLASMA; HIBRIDOS; INVESTIGACION; AFRICA